2023
DOI: 10.5603/fm.a2022.0108
|View full text |Cite
|
Sign up to set email alerts
|

A three-headed piriformis muscle: an anatomical case study and narrative review of literature

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…The absence of the piriformis muscle has been described by authors such as Brenner et al and Leal et al [17,18]. Lastly, the piriformis has been reported to have rarely, two heads with possible attachments to the sacrotuberous ligament, sacrum, or ilium, and recently, in a single case report, three heads but without splitting of the sciatic nerve such as was identified in the case presented herein [19]. The size of the three heads in our case compared to that of Kozioł et al [19] was comparable although the middle head in our case was shorter.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The absence of the piriformis muscle has been described by authors such as Brenner et al and Leal et al [17,18]. Lastly, the piriformis has been reported to have rarely, two heads with possible attachments to the sacrotuberous ligament, sacrum, or ilium, and recently, in a single case report, three heads but without splitting of the sciatic nerve such as was identified in the case presented herein [19]. The size of the three heads in our case compared to that of Kozioł et al [19] was comparable although the middle head in our case was shorter.…”
Section: Discussionsupporting
confidence: 66%
“…Lastly, the piriformis has been reported to have rarely, two heads with possible attachments to the sacrotuberous ligament, sacrum, or ilium, and recently, in a single case report, three heads but without splitting of the sciatic nerve such as was identified in the case presented herein [19]. The size of the three heads in our case compared to that of Kozioł et al [19] was comparable although the middle head in our case was shorter. Additionally, Deopujari et al reported a three-headed piriformis found in a cohort of 21 cadavers [20].…”
Section: Discussionsupporting
confidence: 58%
“…There is a significant lack of data regarding the variable anatomy of the IGA. The arterial anatomy of the pelvis is known for being highly variable, making it a difficult area to operate in [12,16,26,27]. The origin of the IGA has not been sufficiently studied in the past, even though its highly relevant in embolization procedures for pseudoaneurysms [13].…”
Section: Introductionmentioning
confidence: 99%
“…The complex and variable nature of the arterial structure in the pelvic region poses challenges for surgical procedures in this area [4,9,13,14,17,21,24,26,27]. The anatomical aspects of the SGA have been discussed in the past.…”
Section: Introductionmentioning
confidence: 99%